An Automated Machine Learning Approach For Smart Waste Management System - Dr. Madhavi Pingili , M. Bindhu, L.Ramesh, P.Akhil Reddy, Vamsi Krishna Goud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The idea of using waste management systems in an organisation to dispose of, reduce, reuse, and prevent waste is known as this. Recycling, composting,incineration, landfills, bioremediation, energy waste, and waste minimization are a few ways to dispose of garbage. This article demonstrateshow automated machine learning can be used to solve an issue using real-world waste management techniques.Because of our consumption habits and the shifting socioeconomic landscape, good and efficient waste management techniques have become challenging. Technology, economics, sociocultural activities, and political activities must all come together to solve the challenge of waste management.This article specifically focuses on the use of sensor measurements to identify recycle containers. The techniques that we looked into used pre-existing manually designed models, their changes, as well as traditional machine learning algorithms and techniques.The implemented approach makes use of a Random forest classifier on a number of characteristics based on filling level at various time intervals.